Gastroprotective Effect of Ethanol Extracts from Bark of Magnolia officinalis on Ethanol-Induced Gastric Mucosal Damage in Rats. (1st June 2021) - Wang, Xiao; Fu, Shu; Zhang, Chen; Nie, Xin; Liao, Wan; Zhao, Ming; Liu, Fang
Abstract : Background. Magnolia officinalis Rehd. and Wils. is widely used in Asian countries because of its multiple pharmacological effects. This study investigated the gastroprotective effect and mechanisms of the ethanol extracts from the bark of Magnolia officinalis (MOE) against ethanol-induced gastric mucosal damage in rats. Methods. MOE was prepared by reflux extraction with 70% ethanol, and its main compounds were analyzed by UPLC-Q-Exactive Orbitrap-MS. DPPH, ABTS, and FRAP methods were used to evaluate the antioxidant capacity of MOE in vitro . The gastroprotective effects of MOE were evaluated by the area of gastric injury, H&E (hematoxylin-eosin), and PAS (periodic acid-Schiff). The mechanism was explored by measuring the levels of cytokines and protein in the NF- κ B signaling pathway. Results. 30 compounds were identified from MOE, mainly including lignans and alkaloids. MOE presented a high antioxidant activity in several oxidant in vitro systems. Gastric ulcer index and histological examination showed that MOE reduced ethanol-induced gastric mucosal injury in a dose-dependent manner. MOE pretreatment significantly restored the depleted activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) enzymes, reduced malondialdehyde (MDA), and prostaglandin E2 (PGE2) levels in the gastric tissue in rats. In addition, MOE also inhibited the activation of nuclear factor kappa B (NF- κ B) pathway and decreased the production of proinflammatory cytokines. Conclusions. The gastroprotective effect of MOE was attributed to the inhibition of oxidative stress and the NF- κ B inflammatory pathway. The results provided substantial evidence that MOE could be a promising phytomedicine for gastric ulcer prevention.